A CZTSSe thin film solar cell and its preparation method

By introducing the ITO passivation layer between the MO back -back electrode layer of the CZTSSE thin film solar cell and the CZTSSE absorption layer, it solves the problem of low conversion efficiency, achieves a significant effect of improving photoelectric conversion efficiency, and promotes the improvement of solar cell performance.

CN119069551BActive Publication Date: 2025-01-28INNER MONGOLIA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411554009.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

At present, the conversion efficiency of copper-zinc-tin-sulphur-selenium (CZTSSe) thin-film solar cells is low and has not been commercialized, resulting in low solar energy utilization and lacking high cost-effectiveness.

Method used

ITO passivation layers are introduced between the MO back electrode layer and the CZTSSE absorption layer, and the IN2O3 • SNO2 material is used as the passivation layer to improve the contact between the back electrode layer and the absorption layer, thereby improving the optical conversion efficiency.

Benefits of technology

By introducing the ITO passivation layer, the photoelectric conversion efficiency of the CZTSSE thin film solar cell has been significantly improved, the quality of the back interface is improved, and the preparation of high -performance solar cells is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069551B_ABST
    Figure CN119069551B_ABST
Patent Text Reader

Abstract

The invention discloses a CZTSSe thin-film solar cell and a preparation method thereof, which relate to the technical field of solar cells. The CZTSSe thin-film solar cell comprises: a substrate layer; a Mo back electrode layer, which is deposited on the upper surface of the substrate layer; an ITO passivation layer, which is deposited on the upper surface of the Mo back electrode layer; a CZTSSe absorption layer, which is deposited on the upper surface of the ITO passivation layer; a CdS buffer layer; a first window layer and a second window layer; a metal electrode is further arranged on the second window layer; the CZTSSe thin-film solar cell provided by the invention successfully prepares the CZTSSe thin-film solar cell by using a material which is traditionally only used as a solar cell window layer as a passivation layer between the Mo back electrode layer and the CZTSSe absorption layer, and the photoelectric conversion efficiency of the CZTSSe thin-film solar cell is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and more specifically, to a CZTSSe thin-film solar cell and a preparation method thereof. Background Art

[0002] In recent years, due to excessive energy consumption and increasing environmental pollution, the use and development of renewable energy has become increasingly urgent, bringing huge opportunities for various new energy technologies. Among the many renewable energy sources, solar energy is one of the important development directions.

[0003] At present, thin-film solar cells have become the mainstream of development trends. Copper zinc tin sulfur selenium (Cu2ZnSn(S,Se)4, CZTSSe) thin-film solar cells have the advantages of low cost, non-toxicity, high stability, and high theoretical conversion efficiency. They are expected to become thin-film solar cells with wider applications and lower costs, and have great potential for future development.

[0004] However, the conversion efficiency of most copper-zinc-tin-sulfur thin-film batteries currently produced is low, far from the theoretical conversion efficiency, and is not commercialized at present. Even if used on a large scale, the utilization rate of solar energy is not high and does not have a high cost-effectiveness. How to further improve the conversion efficiency of CZTSSe thin-film solar cells is an urgent problem to be solved. Summary of the invention

[0005] In view of this, one of the objects of the present invention is to provide a CZTSSe thin-film solar cell; the present invention successfully prepares a CZTSSe thin-film solar cell by arranging an ITO passivation layer between the Mo back electrode layer and the CZTSSe absorption layer, that is, using the material that is traditionally only used as a window layer of a solar cell as a passivation layer between the Mo back electrode layer and the CZTSSe absorption layer, and its photoelectric conversion efficiency is significantly improved.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A CZTSSe thin film solar cell, comprising:

[0008] basal layer;

[0009] A Mo back electrode layer, wherein the Mo back electrode layer is deposited on the upper surface of the substrate layer;

[0010] An ITO passivation layer, the ITO passivation layer is deposited on the upper surface of the Mo back electrode layer, and the material of the ITO passivation layer is specifically In2O3•SnO2; in terms of mass percentage, it is obtained by mixing 90% In2O3 and 10% SnO2;

[0011] A CZTSSe absorption layer, wherein the CZTSSe absorption layer is deposited on the upper surface of the ITO passivation layer; wherein CZTSSe is a copper zinc tin sulfur selenium thin film;

[0012] A CdS buffer layer, wherein the CdS buffer layer is deposited on the upper surface of the CZTSSe absorption layer;

[0013] A first window layer, wherein the first window layer is deposited on an upper surface of the CdS buffer layer;

[0014] a second window layer, wherein the second window layer is deposited on an upper surface of the first window layer;

[0015] A metal electrode is also disposed on the second window layer.

[0016] Furthermore, the thickness of the ITO passivation layer is 5-20 nm.

[0017] In the present invention, the thickness of the Mo back electrode layer is 800-1000nm; the thickness of the CZTSSe absorption layer is 1.0-2.0 μm; and the thickness of the CdS buffer layer is about 50nm.

[0018] Furthermore, the first window layer is made of ZnO material; the second window layer is also made of ITO material.

[0019] The thickness of the first window layer ZnO is 40-60nm; the thickness of the second window layer ITO is 200-250nm.

[0020] A second object of the present invention is to provide a method for preparing any of the above-mentioned CZTSSe thin film solar cells, comprising the following steps:

[0021] (1) washing and drying the soda-lime glass coated with the Mo back electrode layer; wherein the soda-lime glass is the base layer;

[0022] (2) forming an ITO passivation layer by vacuum radio frequency sputtering deposition on the pretreated Mo back electrode layer;

[0023] (3) Depositing a CZTSSe absorption layer on the ITO passivation layer;

[0024] (4) Depositing a CdS buffer layer on the CZTSSe absorber layer;

[0025] (5) A first window layer and a second window layer are sequentially deposited on the CdS buffer layer, and then a metal electrode is deposited on the second window layer.

[0026] The metal electrode may specifically be an Ag metal electrode with a thickness of about 100 nm.

[0027] Furthermore, in step (1), the cleaning and drying pretreatment is specifically as follows:

[0028] S11, placing the Mo-coated soda-lime glass on a polytetrafluoroethylene bracket; then, placing the polytetrafluoroethylene bracket in a beaker, injecting deionized water into the beaker, and ensuring that the deionized water completely covers the bracket; then, sealing the mouth of the beaker with a plastic wrap, and placing the sealed beaker in an ultrasonic cleaning machine for 10-20 minutes; after the ultrasonic cleaning is completed, taking out the polytetrafluoroethylene bracket, and rinsing the Mo-coated soda-lime glass with deionized water to remove surface impurities;

[0029] S12, placing the polytetrafluoroethylene stent with the Mo-plated soda-lime glass in a beaker, injecting anhydrous ethanol into the beaker to ensure that the stent is completely covered by the anhydrous ethanol; then, sealing the beaker mouth with plastic wrap, placing the sealed beaker in an ultrasonic cleaning machine for 10-20 minutes; after the ultrasonic cleaning, taking out the polytetrafluoroethylene stent, and rinsing the Mo-plated soda-lime glass with deionized water to remove surface impurities;

[0030] S13, repeat step S11;

[0031] S14, placing the cleaned Mo-plated soda-lime glass in a constant temperature drying oven at 60-70° for drying, and storing it for use.

[0032] Furthermore, step (2) is specifically as follows:

[0033] S21. Start the thin film radio frequency sputtering instrument and run it until the vacuum degree of the vacuum chamber reaches 6.0×10-5 Pa. After breaking the vacuum, open the vacuum chamber and clean the vacuum chamber.

[0034] S22, placing the cleaned and dried Mo-coated soda-lime glass on a sample mask, cleaning the surface of the Mo-coated soda-lime glass, and then fixing the mask on a substrate in a vacuum chamber;

[0035] S23, clean the sealing strip of the vacuum chamber, and wipe the sealing strip with a dust-free cloth dipped in anhydrous alcohol. After the alcohol evaporates completely, close the vacuum chamber and perform the machine vacuum extraction process;

[0036] S24, when the vacuum gauge shows that the vacuum degree of the vacuum chamber reaches 6.0×10 -5 When the vacuum gauge is turned off, the argon valve of the vacuum chamber is opened to introduce argon gas, and the argon gas flow rate is set to 30-50 sccm;

[0037] S25, after the argon gas flow rate is stable, the vacuum chamber working pressure is controlled to 2-5 pa, and the substrate rotation speed is adjusted to 3-7 rpm;

[0038] S26, turn on the RF sputtering source, select the target material ITO, set the RF sputtering power to 80-120 W; after the power source is stable, set the ignition pressure to 0.3-0.6 Pa, and perform pre-sputtering for 500-700 seconds; at this time, the target material ITO is sputtered on the baffle, mainly to create a stable and better source condition, so that the sputtered target material ITO can gradually stabilize;

[0039] S27. After the pre-sputtering is completed, the baffle is opened and sputtering is performed for 26-104 seconds to obtain an ITO semiconductor film with a thickness of 5-20 nm, namely, an ITO passivation layer.

[0040] Furthermore, in step S24, the argon gas flow rate is set to 40 sccm.

[0041] Furthermore, in step S25, the argon working pressure is 3 Pa; and the substrate rotation speed is 5 rpm.

[0042] Furthermore, in step S26, the RF sputtering power is 100 W, the ignition pressure is 0.4 Pa, and the pre-sputtering time is 600 s.

[0043] Further, in the present invention, in step S27, after the pre-sputtering is completed, the baffle is opened, and in the first half of the sputtering time, the RF sputtering power is adjusted to 110-120W, and the vacuum chamber working pressure is 2Pa; in the second half of the sputtering time, the RF sputtering power is adjusted to 80-100W, and the vacuum chamber working pressure is 4Pa. The obtained ITO passivation layer has a double-layer structure, the bottom layer can be closely attached to the Mo back electrode layer, and the adhesion to the Mo back electrode layer is improved; the top layer is a relatively loose ITO passivation layer in contact with the CZTSSe absorption layer, which can reduce the resistance of the back electrode.

[0044] Compared with the prior art, the present invention has the following advantages:

[0045] The CZTSSe thin-film solar cell provided by the present invention is successfully prepared by arranging an ITO passivation layer between the Mo back electrode layer and the CZTSSe absorption layer, that is, using a material that is traditionally only used as a solar cell window layer as a passivation layer between the Mo back electrode layer and the CZTSSe absorption layer, and its photoelectric conversion efficiency is significantly improved;

[0046] In the preparation method, the electrical transmission performance is controlled by adjusting the sputtering power, argon gas flow rate, substrate temperature and sputtering time, and the method has strong controllability, good repeatability and can achieve large-area preparation; that is, by reasonably controlling various vacuum radio frequency sputtering parameters, an ITO passivation layer with optimal thickness and performance is obtained. The ITO passivation layer prepared by this method is smooth, dense and uniform, and has the characteristics of high transmittance, low resistivity and high conductivity; the quality of the Mo / CZTSSe back interface is improved, and the CZTSSe thin-film solar cell with the best performance can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The sputtering power was 100 W, the argon flow rate was 40 sccm, the substrate temperature was 0 °C, the substrate speed was 5 rpm, the working pressure was 0.4 Pa, and the initial vacuum was 6.0×10 -5 Pa, XRD pattern of ITO film obtained at sputtering time of 1500 s.

[0048] Figure 2 Schematic diagram of radio frequency sputtering of ITO semiconductor film.

[0049] Figure 3 The morphology images obtained by scanning electron microscopy (SEM) characterization of the Mo / ITO / CZTSSe back interface films prepared under different sputtering time conditions.

[0050] Figure 4 Schematic diagram of the cross section of the final CZTSSe thin film solar cell.

[0051] Figure 5 JV curves of CZTSSe solar cells with ITO passivation layer and CZTSSe solar cells with ITO passivation layer of optimal thickness. DETAILED DESCRIPTION

[0052] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0053] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0054] Example 1

[0055] Step 1. Material pretreatment

[0056] (1) Place the Mo-coated soda-lime glass on a rinsed polytetrafluoroethylene bracket, where the thickness of Mo is 900nm and the thickness of the soda-lime glass is 2mm. Then, place the polytetrafluoroethylene bracket in a clean beaker and inject sufficient deionized water into the beaker to ensure that the deionized water completely covers the bracket. After that, seal the mouth of the beaker with plastic wrap to ensure that it does not come into contact with dust in the outside air. Place the sealed beaker in an ultrasonic cleaner for 10 minutes. After the ultrasonic treatment, remove the polytetrafluoroethylene bracket and rinse the Mo-coated soda-lime glass with clean deionized water to remove surface impurities.

[0057] (2) Place the polytetrafluoroethylene bracket with the Mo-coated soda-lime glass in a clean beaker and inject sufficient anhydrous ethanol into the beaker to ensure that the bracket is completely covered by the anhydrous ethanol. Then, seal the mouth of the beaker with plastic wrap to ensure that it does not come into contact with dust in the outside air. Place the sealed beaker in an ultrasonic cleaner for 10 minutes. After the ultrasonic cleaning is completed, remove the polytetrafluoroethylene bracket and rinse the Mo-coated soda-lime glass with clean deionized water to remove surface impurities.

[0058] (3) Place the polytetrafluoroethylene bracket with the Mo-coated soda-lime glass in a clean beaker and inject sufficient deionized water into the beaker to ensure that the deionized water completely covers the bracket. Then, seal the mouth of the beaker with plastic wrap to ensure that it does not come into contact with dust in the outside air. Place the sealed beaker in an ultrasonic cleaner for 10 minutes. After the ultrasonic cleaning is completed, remove the polytetrafluoroethylene bracket and rinse the Mo-coated soda-lime glass with clean deionized water to remove surface impurities.

[0059] (4) Finally, the cleaned Mo-coated soda-lime glass is placed in a constant temperature drying oven at 60° to dry and stored for use.

[0060] Step 2. Sputtering preparation

[0061] (1) The thin film RF sputtering instrument uses a CIGS thin film solar cell production system and is turned on and operated until the vacuum degree of the vacuum chamber reaches 6.0×10 -5 After Pa, the vacuum chamber is opened after the vacuum is broken.

[0062] (2) Use a vacuum cleaner to clean the inside of the vacuum chamber without any dead corners to avoid residual contamination from different materials in the chamber and improve the quality of thin film formation.

[0063] (3) Place the prepared cleaned soda-lime glass on the sample mask, use an ear-cleaning bulb to blow the surface of the glass to remove dust particles that may have adhered during the operation, and then fix the mask on the substrate in the vacuum chamber.

[0064] (4) Use a vacuum cleaner to clean the sealing strip of the vacuum chamber, and use a dust-free cloth dipped in anhydrous alcohol to wipe the sealing strip. After the alcohol evaporates completely, close the vacuum chamber and proceed with the machine vacuum extraction process.

[0065] (5) When the vacuum gauge shows that the vacuum degree of the vacuum chamber reaches 6.0×10 -5 When 0.04 Pa, turn off the vacuum gauge, open the argon valve in the vacuum chamber, and set the sputtering argon gas flow rate to 40 sccm according to the experimental requirements.

[0066] (6) After the argon gas flow rate stabilizes, set the vacuum chamber operating pressure to 3 Pa, set the substrate speed to 5 rpm and the substrate temperature to 0 °C according to the experimental requirements.

[0067] Step 3. Sputtering

[0068] (1) Turn on the RF sputtering source, select the target material ITO, and set the RF sputtering power to 100 W according to the experimental requirements.

[0069] (2) After the power source is stable, set the ignition pressure to 0.4 Pa and perform pre-sputtering for 600 s.

[0070] (3) After the pre-sputtering is completed, the baffle is opened and sputtering is performed for 1500 seconds as required by the experiment to obtain an ITO semiconductor film.

[0071] (4) After sputtering is completed, according to the machine operation requirements, close the baffle / RF sputtering source / argon valve / substrate speed, break the vacuum, take out the sample, and obtain an ITO semiconductor film with a thickness of about 250 nm.

[0072] The XRD test results are as follows Figure 1 It should be noted that, in the subsequent embodiments of the present invention, the sputtering time for forming the ITO passivation layer is short, and the formed ITO film is too thin to measure the XRD diffraction pattern. Therefore, in this embodiment, the XRD diffraction pattern is measured by sputtering for 1500s, and the obtained ITO film is amorphous.

[0073] Example 2

[0074] like Figure 2 , which is a schematic diagram of RF sputtering of ITO semiconductor film; in this embodiment, compared with embodiment 1, the difference is that in step 3, after the pre-sputtering is completed, the baffle is opened, and sputtering is performed for 0s, 26s, 52s, 78s, and 104s respectively according to the experimental requirements, and ITO passivation layers with thicknesses of 0nm, 5nm, 10nm, 15nm, and 20nm are respectively sputtered;

[0075] Then, CZTSSe absorption layers are deposited on the ITO passivation layers with different thicknesses to obtain a plurality of Mo / ITO / CZTSSe back interface films with different ITO passivation layer thicknesses.

[0076] Among them, the preparation method of the CZTSSe absorption layer is as follows: first, a CZTS precursor solution is prepared in the air, and the specific steps are as follows: first, 1.084 g C4H6CuO4·H2O and 0.74 g SnCl2·2H2O are added to 10.79 mL of DMF and stirred until completely dissolved. Subsequently, 2.126 g SC(NH2)2 is added to the above solution and continued to be stirred until completely dissolved. Finally, 0.61 g ZnCl2 is added and stirred until completely dissolved to obtain a CZTS precursor solution. In a glove box filled with nitrogen, the CZTS precursor solution is dripped onto the back electrode coated with Mo / ITO. Spin coating is performed using a spin coating instrument, and the rotation speed is set to 3000 r / min and the rotation time is 30 s. After the spin coating step is completed, the sample is placed on a hot plate at 300°C and baked for 3 min. Repeat the above spin coating and baking steps 10 times to obtain a CZTS precursor film. The prepared CZTS precursor film was placed in a graphite box filled with selenium particles, and the graphite box was placed in a rapid annealing furnace (RTP). In a nitrogen atmosphere at normal pressure, the temperature was quickly raised to 550°C and maintained for 900 s, followed by natural cooling, and finally a CZTSSe absorption layer film was obtained on the back electrode coated with Mo / ITO.

[0077] The obtained Mo / ITO / CZTSSe back interface films were characterized by scanning electron microscopy (SEM). Figure 3 As shown in the figure, the morphology of the CZTSSe absorption layer with different thickness of ITO passivation layer, it can be seen that the back interface quality of the CZTSSe film with a sputtering time of 52s and a thickness of 10nm is the best. Under this condition, the contact between the back interface and the CZTSSe absorption layer is the closest and has no holes, thus achieving the improvement of the Mo / CZTSSe back interface quality.

[0078] Further, a CdS buffer layer, a ZnO window layer, an ITO window layer and an Ag metal electrode are continuously deposited on the CZTSSe back interface film, wherein the thickness of the CdS buffer layer is about 50 nm, the thickness of the ZnO window layer is about 50 nm, the thickness of the ITO window layer is about 250 nm, and the thickness of the Ag metal electrode is about 100 nm; CZTSSe thin film solar cells with different thicknesses of the ITO passivation layer are prepared, and the schematic cross-sectional view of the battery is shown in FIG. Figure 4 shown.

[0079] The performance of CZTSSe thin film solar cells with an ITO passivation layer thickness of 10 nm (obtained by sputtering for 52 s) (named ITO-52s) was compared with that of CZTSSe thin film solar cells with an ITO passivation layer thickness of 0 nm (named ITO-0s). Figure 5 As shown in the figure, the results show that by introducing an ITO passivation layer on the back interface, the photoelectric conversion efficiency of CZTSSe solar cells has been significantly improved from 8.9% to 10.1%, and high-performance CZTSSe thin-film solar cells have been successfully prepared. This discovery not only verifies the role of the ITO passivation layer in improving battery performance, but also provides new directions and ideas for the future research and development of high-efficiency solar cells.

[0080] Example 3

[0081] The difference between this embodiment and embodiment 2 is that in step 3, after the pre-sputtering is completed, the baffle is opened and sputtering is performed for 52 seconds according to the experimental requirements.

[0082] At this time, the parameters for the first 26 s of sputtering were: the vacuum chamber working pressure was 2 Pa, and the RF sputtering power was set to 120 W;

[0083] The parameters during the last 26 seconds of sputtering were: the vacuum chamber operating pressure was 4 Pa, and the RF sputtering power was set to 80 W.

[0084] Then, a CZTSSe thin film solar cell was prepared using the same method and its performance was tested, and its photoelectric conversion efficiency was 10.9%.

[0085] Comparative Example 1

[0086] The difference between this embodiment and embodiment 2 is that:

[0087] In step 2, the argon injection flow rate is set to 20 sccm; the vacuum chamber working pressure is 1 Pa;

[0088] In step 3, after the pre-sputtering is completed, the baffle is opened and sputtering is performed for 52 seconds according to the experimental requirements to obtain an ITO semiconductor film with a thickness of 10 nm, that is, an ITO passivation layer is formed.

[0089] Then, a CZTSSe thin film solar cell was prepared using the same method and its performance was tested, and its photoelectric conversion efficiency was 8.1%.

[0090] Comparative Example 2

[0091] The difference between this embodiment and embodiment 2 is that:

[0092] In step 2, the substrate temperature is 15°C;

[0093] In step 3, after the pre-sputtering is completed, the baffle is opened and sputtering is performed for 52 seconds according to the experimental requirements to obtain an ITO semiconductor film with a thickness of 10 nm, that is, an ITO passivation layer is formed.

[0094] Then, a CZTSSe thin film solar cell was prepared using the same method and its performance was tested, and its photoelectric conversion efficiency was 8.6%.

[0095] Comparative Example 3

[0096] The difference between this embodiment and embodiment 2 is that:

[0097] In step 3, the RF sputtering power is 50 W;

[0098] After the pre-sputtering was completed, the baffle was opened and sputtering was performed for 52 seconds according to the experimental requirements to obtain an ITO semiconductor film with a thickness of 10 nm, that is, an ITO passivation layer was formed.

[0099] Then, a CZTSSe thin film solar cell was prepared using the same method and its performance was tested, and its photoelectric conversion efficiency was 8.7%.

[0100] Comparative Example 4

[0101] The difference between this embodiment and embodiment 2 is that:

[0102] In step 3, after the pre-sputtering is completed, the baffle is opened and sputtering is performed for 52 seconds according to the experimental requirements to obtain a ZTO thin film with a thickness of 10 nm, that is, a ZTO passivation layer is formed.

[0103] Then, a CZTSSe thin film solar cell was prepared using the same method and its performance was tested, and its photoelectric conversion efficiency was 9.4%.

[0104] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A CZTSSe thin film solar cell, characterized in that: include: basal layer; A Mo back electrode layer, wherein the Mo back electrode layer is deposited on the upper surface of the substrate layer; An ITO passivation layer, the ITO passivation layer is deposited on the upper surface of the Mo back electrode layer, and the material of the ITO passivation layer is specifically In2O3•SnO2; in terms of mass percentage, it is obtained by mixing 90% In2O3 and 10% SnO2; A CZTSSe absorption layer, wherein the CZTSSe absorption layer is deposited on the upper surface of the ITO passivation layer; A CdS buffer layer, wherein the CdS buffer layer is deposited on the upper surface of the CZTSSe absorption layer; A first window layer, wherein the first window layer is deposited on an upper surface of the CdS buffer layer; a second window layer, wherein the second window layer is deposited on an upper surface of the first window layer; A metal electrode is also disposed on the second window layer; The method for preparing the CZTSSe thin film solar cell comprises the following steps: (1) Cleaning and drying the soda-lime glass coated with the Mo back electrode layer; (2) forming an ITO passivation layer by vacuum radio frequency sputtering deposition on the pretreated Mo back electrode layer; (3) Depositing a CZTSSe absorption layer on the ITO passivation layer; (4) Depositing a CdS buffer layer on the CZTSSe absorber layer; (5) depositing a first window layer and a second window layer in sequence on the CdS buffer layer, and then depositing a metal electrode on the second window layer; Among them, step (2) is specifically as follows: S21. Start the thin film RF sputtering instrument and run it until the vacuum degree of the vacuum chamber reaches 6.0×10 -5 After Pa, the vacuum chamber is opened after the vacuum is broken and the vacuum chamber is cleaned; S22, placing the cleaned and dried Mo-coated soda-lime glass on a sample mask, cleaning the surface of the Mo-coated soda-lime glass, and then fixing the mask on a substrate in a vacuum chamber; S23, clean the sealing strip of the vacuum chamber, and wipe the sealing strip with a dust-free cloth dipped in anhydrous alcohol. After the alcohol evaporates completely, close the vacuum chamber and perform the machine vacuum extraction process; S24, when the vacuum gauge shows that the vacuum degree of the vacuum chamber reaches 6.0×10 -5 When the vacuum gauge reaches Pa, the argon valve of the vacuum chamber is opened to introduce argon gas, and the argon gas flow rate is set to 30-50 sccm; S25, after the argon gas flow rate is stable, the working pressure of the vacuum chamber is controlled to be 2-5 pa, the substrate speed is adjusted to be 3-7 rpm, and the substrate temperature is -5°C-5°C; S26, turn on the RF sputtering source, select the target material ITO, set the RF sputtering power to 80-120 W; after the power source is stable, set the ignition pressure to 0.3-0.6 Pa, and perform pre-sputtering for 500-700 seconds; S27. After the pre-sputtering is completed, the baffle is opened and sputtering is performed for 26-104 seconds to obtain an ITO semiconductor film, namely, an ITO passivation layer.

2. The CZTSSe thin film solar cell according to claim 1, characterized in that: The thickness of the ITO passivation layer is 5-20 nm.

3. The CZTSSe thin film solar cell according to claim 1, characterized in that: The first window layer is made of ZnO material; the second window layer is also made of ITO material.

4. The CZTSSe thin film solar cell according to claim 1, characterized in that: In step (1), the cleaning and drying pretreatment is specifically as follows: S11, placing the Mo-coated soda-lime glass on a polytetrafluoroethylene bracket; then, placing the polytetrafluoroethylene bracket in a beaker, injecting deionized water into the beaker, and ensuring that the deionized water completely covers the bracket; then, sealing the mouth of the beaker with a plastic wrap, and placing the sealed beaker in an ultrasonic cleaning machine for 10-20 minutes; after the ultrasonic cleaning is completed, taking out the polytetrafluoroethylene bracket, and rinsing the Mo-coated soda-lime glass with deionized water to remove surface impurities; S12, placing the polytetrafluoroethylene stent with the Mo-plated soda-lime glass in a beaker, injecting anhydrous ethanol into the beaker to ensure that the stent is completely covered by the anhydrous ethanol; then, sealing the beaker mouth with plastic wrap, placing the sealed beaker in an ultrasonic cleaning machine for 10-20 minutes; after the ultrasonic cleaning, taking out the polytetrafluoroethylene stent, and rinsing the Mo-plated soda-lime glass with deionized water to remove surface impurities; S13, repeat step S11; S14, placing the cleaned Mo-plated soda-lime glass in a constant temperature drying oven at 60-70° for drying, and storing it for use.

5. The CZTSSe thin film solar cell according to claim 1, characterized in that: In step S24, the argon gas flow rate is set to 40 sccm.

6. The CZTSSe thin film solar cell according to claim 1, characterized in that: In step S25, the working pressure is 3 Pa, the substrate rotation speed is 5 rpm, and the substrate temperature is 0°C.

7. The CZTSSe thin film solar cell according to claim 1, characterized in that: In step S26, the RF sputtering power is 100 W, the ignition pressure is 0.4 Pa, and the pre-sputtering time is 600 s.

Citation Information

Patent Citations

  • CIS / CIGS solar cell having a rear TCO layer and production method therefor

    CN103477442A